Microstructural analysis of a1-mg-si-zn alloy (2010)
As a part of an overall effort to develop a new A1-alloy appropriated for structural applications, a characterization research was directed towards the development of microstructure and their relationship with heat treatment. The A1-Mg-Si-Zn was chose for that purpose due to the presence of precipitates in α-A1 matrix and at grain boundaries, capable to get an excellent relationship between hardness and mechanical resistance. With regards to microstructure, this was characterized in the as-cast and as-aged condition. This treatment was carried out in two stages, the first one at 450ºC during 3 hr which correspond to homogenization treatment and the second one, the ageing treatment at 160 ºC 1hr. Results of microstructure characterization in the ascast ingots showed the α-A1 dendrites, and in addition the presence of a binary eutectic and particles of Mg₇Zn₃ type in interdendritic regions. The eutectic and particles were modified by the aged treatment. Transmission electron microscopic observations carried out in specimens with and without heat treatments showed a uniform distribution of precipitates with different morphologies like cubic, spherical and platelet; in the matrix, which were no detected during the scanning electron microscope observations.